2022
DOI: 10.1097/j.jcrs.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser–assisted descemetorhexis for Descemet membrane endothelial keratoplasty: cell-based and tissue-based ex vivo analysis of precision and safety

Abstract: To analyze precision and safety of femtosecond laser-assisted descemetorhexis and postoperative corneal wound healing in human ex vivo specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…5,6 The femtosecond incisions were found to cause minimal endothelial damage. 7 Our group has also shown reduced endothelial cell loss (ECL) in F-DMEK compared with M-DMEK over the early postoperative period. 6 To the best of our knowledge, there are no published data on 5-year safety and efficacy of F-DMEK.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…5,6 The femtosecond incisions were found to cause minimal endothelial damage. 7 Our group has also shown reduced endothelial cell loss (ECL) in F-DMEK compared with M-DMEK over the early postoperative period. 6 To the best of our knowledge, there are no published data on 5-year safety and efficacy of F-DMEK.…”
mentioning
confidence: 73%
“…Feldhaus et al 7 recently performed a cell-based and tissue-based ex vivo analysis of the influence femtosecond descemetorhexis has on the endothelium and found that the laser has a minimal impact on the vitality of the treated tissue, especially regarding the corneal endothelium. Compared with M-DMEK, the F-DMEK procedure seems to induce less ECL in patients with FED.…”
Section: Discussionmentioning
confidence: 99%
“…[ 66 ] In DMEK, FSL can enable descemetorhexis with desired size and depth with excellent accuracy that results in the precise apposition between host and donor endothelial tissue without graft-host tissue overlap, which may be associated with a reduced risk of graft detachment and rebubbling. [ 14 , 15 , 67 ] Sorkin et al . [ 68 , 69 ] reported that FSL-assisted DMEK showed excellent efficacy and safety over 5 years of follow-up.…”
Section: Femtosecond Laser-assisted Endothelial Keratoplastymentioning
confidence: 99%